Le fonctionnement morphosyntaxique de l’adjectif qualificatif en isángu (langue bantu du groupe B40 parlée en République du Gabon) - Simpson Dorothy MBADINGA MBADINGA (Revue Hybrides)
This article proposes to study the morphosyntactic functioning of the qualifying adjective in Isangu, a language localized in Gabon, spoken by Masangu speakers. In this language, we identify two types of qualifying adjectives: those that admit agreement and those that are invariable. The qualifying adjective is apt to assume the function of attribute and the function of determining noun depending on the context.